Controllable Formation of Niobium Nitride/Nitrogen‐Doped Graphene Nanocomposites as Anode Materials for Lithium‐Ion Capacitors. (9th September 2015) - Liu, Meng; Zhang, Lixue; Han, Pengxian; Han, Xiaoqi; Du, Huiping; Yue, Xiaoyue; Zhang, Zhongyi; Zhang, Hui; Cui, Guanglei
Abstract : Niobium nitride/nitrogen‐doped graphene nanosheet hybrid materials are prepared by a simple hydrothermal method combined with ammonia annealing and their electrochemical performance is reported. It is found by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) that the as‐obtained niobium nitride nanoparticles are about 10–15 nm in size and homogeneously anchored on graphene. A non‐aqueous lithium‐ion capacitor is fabricated with an optimized mass loading of activated carbon cathode and the niobium nitride/nitrogen‐doped graphene nanosheet anode, which delivers high energy densities of 122.7–98.4 W h kg −1 at power densities of 100–2000 W kg −1, respectively. The capacity retention is 81.7% after 1000 cycles at a current density of 500 mA g −1 . The high energy and power of this hybrid capacitor bridges the gap between conventional high specific energy lithium‐ion batteries and high specific power electrochemical capacitors, which holds great potential applications in energy storage for hybrid electric vehicles. Abstract : Niobium nitride/nitrogen‐doped graphene nanocomposites (NbN/NG) as anode materials for lithium‐ion capacitors possess excellent electrochemical performance. An appropriate amount of NbN in the hybrid materials is beneficial to form a synergistic structure and thus improve rate performance and specific capacity.